PENERAPAN METODE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI ATPH PADA MATERI TEKNIK PEMANENAN HASIL TANAMAN SAYURAN DI SMK NEGERI BEUNGGA - Chumaidi Chumaidi (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2021)
This research is a Classroom Action Research (CAR) which aims to improve learning outcomes of Vegetable Crop Production Materials for Harvesting Vegetable Crop Products in class XI ATPH SMK Negeri Beungga even semester of the 2020/2021 academic year through the application of the Student Teams Achievement Division (STAD) method. This research was conducted in a collaborative and participatory manner which was carried out in two cycles. Data collection in this study was carried out using participant observation and written tests. Based on the results of the study, it was concluded that the use of the Student Teams Achievement Division (STAD) method could improve student learning outcomes. This is supported by research data which shows an increase in the percentage of completeness of written tests conducted at each meeting in each cycle. At the time of the pre-cycle, the completeness of student learning outcomes was only 29.41% with an average value of 61.17, after the first cycle was carried out with the STAD learning model the percentage of complete student learning outcomes at meeting 1 became 47.05% or 8 students with grades an average of 65.88 then at the second meeting the completeness became 58.82% or 10 students who completed with an average value of 67.64. In the second cycle of action, the first meeting of completeness of learning outcomes reached 76.47% or 13 students who completed with an average score of 76.47 while at the second meeting the completeness of learning became 100% or all students who completed with an average value of 87.64. Thus, the application of the Student Teams Achievement (STAD) method was declared successful in increasing the learning outcomes of Vegetable Crop Production in Materials for Harvesting Vegetable Crops in Class XI ATPH SMK Negeri Beungga for the 2020/2021 academic year.Keywords: Student Teams Achievement Method, Student Learning Outcomes